CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

Please let me know the mistake in this equation: 

-20=-20

16-36=25-45

42  ​​​-4*9=52-5*9

42 - 2*4* 9/2=5-2*5* 9/2

(4-9/2)= (5-9/2)2

4=5


Solution

42 - 2*4* 9/2=5-2*5* 9/2

(4-9/2)= (5-9/2)2


this step is wrong 

correctly 

(4-9/2)^2 = 4^2 -(2*4*9/2) + (9/2)^2 

(5-9/2)^2 = 5^2 -(2*5*9/2) + (9/2)^2 

so you cant write like that

flag
 Suggest corrections
thumbs-up
 
0 Upvotes


Similar questions
View More


People also searched for
View More



footer-image